"Piękny" - "pięknie" - "piękno". Eksplikacja znaczeń i profili pojęcia piękna na podstawie wyników analizy korpusowej = "Piękny" - "pięknie" - "piękno". The explication of meanigs and profiles of the notion of beauty. Corpus-based analysis - Szymańska, Monika (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The paper is an attempt at the reconstruction of language image of beauty. The corpus-based analysis was used. It was based on material from National Corpus of the Polish Language in the form of collocations based on expressions "beautiful", "beautifully" and "beauty", which are language exponents of the analyzed notion.
Keywords: profilowanie; analiza korpusowa; kolokacja; profiling; corpus-based analysis; collocation